Does left ventricular hypertrophy identify the increased risk of coronary heart disease among UK Indian Asians?. (22nd September 2015) - Ahmed, N; Kooner, JS; Chambers, JC
Abstract : Background: Coronary heart disease (CHD) mortality is higher among UK Indian Asians than European whites, and is not explained by differences in cigarette smoking, blood pressure, hypercholesterolaemia, diabetes or related metabolic disturbances. Studies in North American and European whites have identified left ventricular hypertrophy (LVH) as an independent risk factor for CHD. The prevalence of LVH and the possible contribution of LVH to increased CHD risk among Indian Asians remain unknown. Methods: We compared the prevalence of LVH among 22 413 Indian Asian and European white men and women aged 35–75 years participating in the London Life Sciences Population (LOLIPOP) study, and recruited from the lists of 58 primary care physicians in west London with a response rate of 62%. Clinical, anthropometric and biochemical data, including waist–hip girth ratio (WHR), fasting glucose and lipid profile were recorded for each subject. A 12-lead ECG was recorded by standardised methodology; ECG were assessed for the presence of LVH, using the Sokolow–Lyon index criteria (sum of SV1 + RV5/V6 >3.5 mV). Results: In comparison with European whites, Indian Asians had lower smoking rates and cholesterol levels, a higher prevalence of hypertension and type 2 diabetes, raised WHR, glucose and triglycerides, and lower high-density lipoprotein cholesterol (see table). The prevalence of LVH was lower among Indian Asians than European whites (2.0% vs 2.6%, p<0.001). LVH was positively correlated with age, male gender, blood pressure, and inversely related to body mass index, WHR and body surface area. In regression analysis, the prevalence of LVH remained lower among Indian Asians than European whites, despite adjustment for differences in age, gender, body mass index, WHR or body surface area between Indian Asians and European whites (odds ratio (OR) 0.78, 95% CI 0.68 to 0.95, p<0.001). Conclusions: As assessed by surface ECG and using Sokolow–Lyon criteria, LVH is less common among Indian Asians than European whites. These findings contrast the strikingly higher prevalence of hypertension and type 2 diabetes, and the approximately twofold increased risk of CHD among Indian Asians compared with European whites. Although further studies are needed to evaluate the sensitivity and specificity of ECG criteria for diagnosing LVH in Indian Asians, our findings demonstrate that LVH (as determined by the surface ECG) does not predict the increased risk of CHD among Indian Asians.